Pleomorphous leiomyosarcoma of the mesocolon: a case report - Jai, Saad Rifki (Pan Afr Med J, 2015)
Leiomyosarcoma is a rare tumor of the smooth muscle, but relatively frequent in the stomach and the small intestine. The mesocolic site is rare. Globally, leimyosarcoma represents less than 0, 1% of the malignant tumors found in the colon and the anus. Because of the similarities with other digestive tumors, namely mesenchymatous or benign tumors of the smooth muscle, the diagnosis of a pleomorphic sarcoma remains difficult even at the histological stage. Surgery is the mainstay of the therapy. We report a case of leiomyosarcoma of the mesocolon and discuss about its main characteristics in the view of the current literature about this pathological condition.